High Speed and Low Leakage Power Voltage Level Shifter using Regulated Cross-Coupled Network - Thokala, Mohan Rao (Journal of Applied Science, Engineering, Technology, and Education, 2023)
This concise presents a power efficient level shifter using regulated cross-coupled network with split inverter. With the use of regulated cross-coupled network, power dissipation of the pull-up region drastically decreases. Level shifters convert the voltage levels which are below the threshold voltage to the acceptable voltage levels by decreasing the transistor size. A Split inverter is used at the output to decrease the short circuit current. Modified Split inverter along with the load capacitor at the output is used to increase the speed and to decrease the power consumption. This LS can save 31% power compared to other techniques. The proposed level shifter works effectively at high speed and consumes less power. For simulation, LT spice tool of 50 nm technology and 90 nm technology is used.